Code Switching in Boy William's YouTube Video “#NebengBoyNewGeneration Eps. 42”: Sociolinguistics Study - Corry Aina; Ervina CM Simatupang (Universitas Nahdlatul Wathan Mataram, 2024)
The research objective is to observe about code-switching in YouTube video. The study delves into the types of code-switching present in the YouTube video titled “GOKIL! TERNYATA CINTA LAURA MASIH CINTA BOY WILLIAM?! #NebengBoyNewGeneration Eps. 42”. It specifically investigates the shifts in code-switching between Boy William and Cinta Laura, as well as explores the reasons behind their use of code-switching. Employing a qualitative approach, the research adopts a descriptive method for analysis. The data are scrutinized using a theoretical framework that identifies code-switching types and reasons in Boy William's video. The analysis of reasons for code-switching in their conversations is grounded in a theory encompassing tag switching, intra-sentential switching, and inter-sentential switching. Additionally, the research identifies five reasons for code-switching in their conversations: Interjection, clarifying the speech content, be emphatic about something, talking about a particular topic, and repetition used for clarification.